An "organizational triangle" to coordinate talent development: A case study in Danish swimming - Winthereik Mathorne, O.; Henriksen, K.; Stambulova, N. (Case Studies in Sport and Exercise Psychology, 2020)
This case study in Danish swimming was informed by a holistic ecological approach in talent development and aimed to explore (a) collaborative relationships between the Danish swimming federation, a municipality, and a local swimming club, termed "an organizational triangle," and (b) factors influencing the success of their collaboration at the local level. Data collection and analysis were guided by the athletic-talent-development-environment (working) model and a newly developed collaboration-success-factors (CSF) model. Methods included interviews with talent-development coordinators representing the organizations and analysis of documents. Results allowed the authors to transform the CSF (working) model into an empirical model containing the collaboration preconditions (e.g., power to make decisions), processes (e.g., strategic planning), and initiatives (e.g., efficient use of the swimming pool) and shared assumptions of the talent-development philosophy (e.g., long-term focus). The success of this organizational triangle was visible in the way the organizations increased the quality of talent development in the local swimming club.